تقويم أداء مدرسي الرياضيات للمرحلة الثانوية على ضوء المعايير المهنية المعاصرة "دراسة ميدانية في محافظة حمص" - الونوس رويدا (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
هَدَفَ البحث الحالي إلى تحديد قائمة بالمعايير المهنية المعاصرة، واللازم توفرها لمدرسي الرياضيات في المرحلة الثانوية في محافظة حمص وتحديد مدى توفر مؤشرات تطبيق هذه المعايير لديهم. من أجل ذلك تم بناء أداتين من إعداد الباحث هنَّ: استبانة تتضمن قائمة بالمعايير المهنية اللازم توفرها من وجهة نظرهم وبطاقة ملاحظة لتحديد مدى توفر هذه المعايير لدى مدرسي رياضيات المرحلة الثانوية. طُبقت الاستبانة على عينة مكونة من (110) مدرس وموجه، وطُبقت بطاقة الملاحظة على (65) مدرس في محافظة حمص. توصل البحث إلى قبول جميع المعايير في الاستبانة بما تحويه من معايير فرعية، فكانت نسبة الموافقة عليها بين (59,09 %و 99،09%). وبالتالي يمكن اعتمادها كمعايير مهنية، توفرها ضروري لمدرسي الرياضيات. وتوصل البحث أيضاً إلى وجود دلالة إحصائية لتوفر (18) معيارٍ مهنيٍّ فرعيٍّ من إجمالي (31) معيارٍ مهنيٍّ فرعيٍّ بدرجةٍ متوسطةٍ، ووجود دلالة إحصائية لتوفر (10) معايير مهنية فرعية من إجمالي (31) معيار بدرجة قليلة. The aim of this research is to establish a list of contemporary professional standards that mathematics’ teachers should have and find out how much they apply those standards. In order to achieve that, two research tools were designed, by the researcher, which were a questionnaire that consist of a list of the professional standards based on the teachers opinion and a note card to determine the extent of these standards availability among high school math teachers. The questionnaire was applied on a sample of (110) teachers and tutors and the note card was applied on (65) teachers in Homs governorate. The result of the research concluded to accept all the standards in the questionnaire including the sub-standards as the agreement on them was between 59.09% and 99.09%. So, they can be used as professional standards that high school’s math teachers should have. Moreover, the results showed that (18) out of (31) of professional sub-standards are statistically significant available in math teachers in an average degree, and (10) out of (31) are available in small degree.